Camere aeree oblique: sistemi, applicazioni e prospettive future - Remondino, Fabio; Nex, Francesco; Toschi, Isabella; Rupnik, Ewelina (GEOmedia, 2014)
The use of oblique imagery has become a standard for many civil and mapping applications, thanks to the development of airborne digital multi-camera systems, as proposed by many companies. The indisputable virtue of oblique photography lies in its simplicity of interpretation and understanding for inexperienced users allowing their use of oblique images in very different applications, such as building detection and reconstruction, building structural damage classification, road land updating and administration services, etc. We report an overview of the actual oblique commercial systems and the workflow for the automated orientation and dense matching of large image blocks. Perspectives, potentialities, pitfalls and suggestions for achieving satisfactory results are given too.